Contribuições ao controle eletrônico inteligente de reguladores de tensão para sistemas de distribuição de energia em 13,8 kV - Lima, Rodrigo Rimoldi de (2007)
The development considered in this work exceeds to the conventional operation until then practised by being based on a microcontrolled electronic circuit that acts on the load of the system for intermediary of 09 taps of regulation (02 of reduction, 06 of rise and the central office) in total independent way and with great speed of reply, rank that the regulation was proceeded in a time limit of 04 cycles of the electric net. Each step of regulation provides a 5% variation on the nominal value of the tension delivers to the load, establishing an ample control for values between 70% and 110% of the supplied signal the same one. The communication of this with the module of mentioned control is made through thyristors (SCR' s) with refrigeration air.